THE WAY OF PRODUCTION OF THE TEETH OF THE CUTTING MECHANISMS OF GRAIN- AND FEED-HARVESTING TECHNIQUE SEGMENTS BY PLASTIC DEFORMING - L. A. Isajevich; D. M. Ivanitskij; V. A. Korol (Литьë и металлургия, 2005)
The development of the technology of the cutting teeth plastic forming on the surface of segment instead of milling is presented.